ANALISIS PERTUMBUHAN DAN DAYA SAING EKONOMI DI PROVINSI RIAU - Hermaleni ' '; Syaiful ' Hadi2; Didi ' Muwardi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this study aims to analyze the rate growth and competitiveness of each province in Indonesia by economic sectors especially in Riau. The methods of analysis used in this study is Shift Share. The results showed that the West Sulawesi has a slow growth rate in agriculture, livestock, forestry and fisheries but is able competitive well, while the sector of electricity, gas and water supply has a rapid growth rate and afford competitive properly. Gorontalo has a slow growth rate but is able competitive well in the mining and quarrying sectors. West Papua growth rate is slow but capable of competitive well in the manufacturing sector, while the services sector has a rapid growth rate and afford competitive properly. Papua has a rapid growth rate and is able competitive well in the building sector and the financial sector, leasing and business services. Southeast Sulawesi has a rapid growth rate and is able competitive well in the trade, hotels and restaurants. DKI Jakarta has a rapid growth rate and is able competitive well in the transport and communications sector. The economic sectors that have rapid growth rate and have high competitiveness in Riau are: the building sector; trading, hotel and restaurant sector; transportation and communication; financial, rental and service company; and services sector. The slow-growing economic sectors and unable to competitive well are: agriculture, livestock, forestry and fishery, and also mining and quarrying.Keywords : Economic Growth, Competitiveness, Shift Share